High‐dose chemotherapy with autologous stem cell transplantation in relapsed or refractory germ cell tumours: outcomes and prognostic variables in a case series of 17 patients. Issue 8 (August 2014) - Lewin, J.; Dickinson, M.; Voskoboynik, M.; Collins, M.; Ritchie, D.; Toner, G.
Abstract Background Optimal therapy for men relapsing after initial chemotherapy for germ cell tumours (GCT) is poorly defined. Both conventional dose salvage regimens and high‐dose chemotherapy with autologous stem cell transplantation (HDCT‐ASCT) have been utilised. Aims To examine patients who received HDCT‐ASCT for relapsed GCT within a single Australian centre. Methods Records between 2000 and 2012 were analysed for baseline characteristics, treatment‐related toxicity and survival. Prognosis at the time of HDCT‐ASCT was classified according to the International Prognostic Factors Study Group (IPFSG). Results Seventeen patients received HDCT‐ASCT, median age 34 (21–46), with 41% having primary refractory disease and 53% with high/very high risk disease by IPFSG. The most common regimen utilised was paclitaxel/ifosfamide followed by high‐dose carboplatin/etoposide (TI‐CE; n = 12). The median duration of grade 4 (G4) neutropenia was 11 days (range 9–17) with febrile neutropenia in 90% resulting in four intensive care unit admissions (8%). Median duration of G4 thrombocytopenia was 10 days (range 8–19) requiring a median of two pooled platelets bags (range 0–33) per episode. Transplant‐related mortality occurred in one patient (veno‐occlusive disease). Twenty‐seven per cent of HDCT‐ASCT cycles were associated with grade 3 mucositis (median total parenteral nutrition days = 5 (0–23)). Two‐year progression‐free survival (PFS) and overall survival (OS) rates were 59% and 71%. Patients who received HDCT‐ASCT as second or subsequent relapse fared worse than those treated with HDCT‐ASCT at first relapse (hazard ratio 0.23 (95% confidence interval: 0.04, 1.37; P‐value 0.09). Three‐year OS for those who received TI‐CE at first relapse was 90%. Conclusions HDCT‐ASCT for relapsed GCT is effective with acceptable toxicity. There was encouraging PFS/OS, particularly in a poor‐prognosis cohort.